STEM-07. THE ATYPICAL METALLOPROTEINASE ADAMDEC1 MAINTAINS A NOVEL FGF MEDIATED SIGNALLING NETWORK IN GLIOBLASTOMA CANCER STEM CELLS. (11th November 2019) - Jimenez-Pascual, Ana; Hale, James; Bayik, Defne; Silver, Daniel; Roversi, Gustavo; Alban, Tyler; McIntyre, Thomas; Colombo, Giorgio; Taraboletti, Giulia; Holmberg, Karl; Forsberg-Nilsson, Karin; Lathia, Justin; et al.
Abstract: Glioblastomas (GBM) are lethal brain tumors where poor outcome is attributed to cellular heterogeneity, therapeutic resistance, and a highly infiltrative nature. These characteristics are preferentially linked to GBM cancer stem cells (CSCs), but how CSCs maintain their stemness is incompletely understood and the subject of intense investigation. CSCs rely both on cell intrinsic programs and microenvironmental interactions to regulate their maintenance. Recent work has demonstrated that CSCs can modulate their surrounding microenvironment by metalloproteinase expression, allowing direct modification of the extracellular matrix that provides structural tissue integrity, and instructive signalling via engagement of key cell surface receptors and sequestration of essential growth factors. Here, we identify a novel growth factor signalling loop that induces and maintains CSCs via an atypical metalloproteinase, a disintegrin and metalloproteinase domain-like protein decysin 1 (ADAMDEC1), secreted by CSCs. ADAMDEC1 solubilizes fibroblast growth factor-2 (FGF2) in the tumor microenvironment. We find that CSCs exclusively express FGF receptor 1 (FGFR1), which upon binding of FGF2 induces upregulation of Zinc finger E-box-binding homeobox 1 (ZEB1). ZEB1 is a regulator of stemness and tumor initiation, and therefore ADAMDEC1-FGF2-FGFR1 signalling promotes malignancy in GBM. We further show that ERK phosphorylation drives ZEB1, which regulates ADAMDEC1 expression, creating a positive feedback loop via repression of microRNA-203. Genetic or pharmacological targeting of components of this axis attenuates self-renewal and tumor growth. These findings reveal a new signalling axis for CSC maintenance and highlight ADAMDEC1 and FGFR1 as potential therapeutic targets in GBM. In addition, these findings provide a new paradigm for GBM growth through which key growth factors embedded within the extracellular matrix can be selectively accessed by CSC for their maintenance.